2020
DOI: 10.1080/00318884.2020.1775461
|View full text |Cite
|
Sign up to set email alerts
|

Genetic data support reproductively isolated species in the endemic Cladophoraceae (Chlorophyta) of Lake Baikal, Russia

Abstract: Ancient lakes are centres of biological diversification that hold many examples of adaptive radiation and species flocks. The recently discovered species flock of Cladophoraceae in Lake Baikal is a group of green algae that exhibit low genetic divergence in ribosomal markers (LSU, SSU, and ITS), but wide morphological differentiation. Microsatellite markers showed evidence of polyploidy in this group, requiring alternate data scoring methodologies. In this study, we use two clustering methods (STRUCTURE and Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…In the study region, P. anomala grows under different ecological conditions and at altitudes (from 700 to 1850 m). Other authors [69][70][71][72] have confirmed the high ecological plasticity of the species. However, the species do not tolerate the excessive overwatering or drying of their habitat.…”
Section: Discussionmentioning
confidence: 53%
“…In the study region, P. anomala grows under different ecological conditions and at altitudes (from 700 to 1850 m). Other authors [69][70][71][72] have confirmed the high ecological plasticity of the species. However, the species do not tolerate the excessive overwatering or drying of their habitat.…”
Section: Discussionmentioning
confidence: 53%